POTENTIALS AND LIMITATIONS FOR THE DEVELOPMENT OF RURAL TOURISM IN VOJVODINA - Bošković, Tatjana; Tomić, Radovan; Danilo, Tomić (Economics of Agriculture, 2013)
The natural attractiveness of rural areas in Vojvodina is a good basis for a rural tourism development. However, the available natural resource base is not sufficient to ensure the rapid and successful development of tourism in rural areas in Vojvodina. In this process all available resources need to be activated. The human and financial resources for rural tourism development in the region of Vojvodina are the subject of this research. The aim of this research is to determine the condition of existing resources and propose measures for their improvement.